2020
DOI: 10.2147/rmhp.s266329
|View full text |Cite
|
Sign up to set email alerts
|

<p>Self-Medication Practices among Undergraduate University Students in Northeast Ethiopia</p>

Abstract: Background: Inappropriate self-medication is a public-health problem worldwide. Major problems associated with self-medication include wastage of resources, increased resistance of pathogens, and adverse drug reactions. Objective: The aim of this study was to assess self-medication practices and associated factors among undergraduate Wollo University students in Northeast Ethiopia. Methods: A cross-sectional study was conducted among 341 undergraduate university students using a pretested and self-administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 25 publications
(49 reference statements)
2
14
1
3
Order By: Relevance
“…The drug classes that are were often used by the students in this study were analgesics (80.5%) followed by antibiotics (52.1%) and proton pump inhibitors (6.9%) were reported to have the lowest prevalence. Studies by Pirzadeh and Mostafavi ( Pirzadeh and Mostafavi, 2014 ), Zewdie ( Zewdie et al, 2020 ), and Tesfaye ( Tesfaye et al, 2020 ) also found that analgesics were mostly self-administered drugs. In contrast, the use of analgesics was higher in our study compared to these other studies.…”
Section: Discussionmentioning
confidence: 93%
“…The drug classes that are were often used by the students in this study were analgesics (80.5%) followed by antibiotics (52.1%) and proton pump inhibitors (6.9%) were reported to have the lowest prevalence. Studies by Pirzadeh and Mostafavi ( Pirzadeh and Mostafavi, 2014 ), Zewdie ( Zewdie et al, 2020 ), and Tesfaye ( Tesfaye et al, 2020 ) also found that analgesics were mostly self-administered drugs. In contrast, the use of analgesics was higher in our study compared to these other studies.…”
Section: Discussionmentioning
confidence: 93%
“…In the present meta-analysis, eight Ethiopian Universities were represented. Eight of the studies were from Amhara [ 27 – 29 , 31 34 , 38 ], three from Oromia [ 30 , 35 , 36 ], and two from Tigray [ 24 , 37 ]. Regarding the response rate, almost all studies had a response rate of greater than 90% (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…To show the association between self-medication and sex of patients, eight studies [ 24 , 28 , 30 34 , 38 ] were selected for meta-analysis. Two studies [ 28 , 30 ] showed, there was a statistically significant association between self-medication and sex and six studies showed that there was no significant association between medication self-practice and sex of the respondents.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations